2020
DOI: 10.1016/j.ymthe.2020.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Immune Modulation by Telomerase-Specific Oncolytic Adenovirus Synergistically Enhances Antitumor Efficacy with Anti-PD1 Antibody

Abstract: The clinical benefit of monotherapy involving immune checkpoint inhibitors (ICIs) such as anti-programmed death-1 antibody (PD-1 Ab) is limited to small populations. We previously developed a telomerase-specific oncolytic adenovirus, Telomelysin (OBP-301), the safety of which was confirmed in a phase I clinical study. Here, we examined the potential of OBP-502, an OBP-301 variant, as an agent for inducing immunogenic cell death (ICD) and synergistically enhancing the efficacy of OBP-502 with PD-1 Ab using CT26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…These results are consistent with the studies by Kanaya et al. 12 and Zhang et al. 14 However, in the present study, the massive infiltration of lymphocytes did not induce a significant antitumor immune response, and the survival of mice was not prolonged, which suggested that there are potential factors that suppress antitumor immunity and hinder the antitumor effect of the oncolytic virus Ad5con; there may also be insufficient activation of immune costimulatory signals, which may disable infiltrating lymphocytes, including T cells.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These results are consistent with the studies by Kanaya et al. 12 and Zhang et al. 14 However, in the present study, the massive infiltration of lymphocytes did not induce a significant antitumor immune response, and the survival of mice was not prolonged, which suggested that there are potential factors that suppress antitumor immunity and hinder the antitumor effect of the oncolytic virus Ad5con; there may also be insufficient activation of immune costimulatory signals, which may disable infiltrating lymphocytes, including T cells.…”
Section: Discussionsupporting
confidence: 94%
“…The oncolytic adenovirus H101 with E1B-55kDa deleted was approved for the treatment of head and neck squamous cell carcinoma in 2005. 5 There are currently multiple oncolytic adenoviruses being studied in clinical 6 , 7 , 8 , 9 , 10 and preclinical research, 11 , 12 , 13 , 14 and these oncolytic adenoviruses have shown some application prospects and have characteristics of oncolytic adenovirus-mediated immunotherapy. First, an oncolytic adenovirus can cause immunogenic cell death (ICD) of tumor cells, leading to the release of damage-associated molecular patterns (DAMPs) and the activation of innate immunity.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have reported that telomerase-specific oncolytic Ad virus such as OBP-301 could induce immunogenic cell death (ICD), which leads to the induction of systemic anti-tumor immune response via the activation of dendritic cells and the facilitation of cytotoxic T lymphocyte recruitment. 48 Therefore, i.p. administration of oncolytic Ad virus treatment might be a promising candidate for combination therapy with immune checkpoint inhibitors (ICIs) in the future.…”
Section: Discussionmentioning
confidence: 96%
“…Even intratumoral injections of OVs have been proved to activate antitumor immunity not only inside tumors and on adjacent TME, but also on distant untreated focuses (62). Previous studies have revealed that oncolytic viruses such as Coxsackievirus B3, Adenovirus, Measles virus, Semliki Forest virus, Newcastle disease virus, influenza A virus elicit ICDs (33,34,(45)(46)(47)50) and improve immune responses of ICBs (48,49). The additional release of pathogen-associated molecular patterns (PAMPs) derived from oncolytic viruses further increases immuneactivation (63).…”
Section: Vaccination With Icd Inducers: Oncolytic Virusesmentioning
confidence: 99%